Handling Times of Patients at a Level-1 Academic Trauma Center - Sayyed Majid Sadrzadeh; Shima Sheibani; Behrang Rezvani Kakhki; Seyed Mohammad Mousavi; Shaghayegh Rahmani; Saeed Eslami; Maryam AkbariLakeh; Elnaz Vafadar Moradi (Patient Safety and Quality Improvement Journal)
Introduction:The patient handling time can affect a patient’s access to critical care; also, there is a relationship between patient handling time in the emergency ward and recovery rates. Nurses and staff of emergency wards are essential factors affecting patient flows in emergency wards. Materials and Methods: This cross-sectional study focused on the flow of patients referring to the level-1 Academic Traumatic Emergency Ward during 2018-2019. Nurses were divided into two categories of group and small-group training, each receiving two training rounds one month apart. The Revised Form of Timing and Workflow Emergency checklist was used for evaluation. Results: Evaluating 600 patients showed that the average time from patient entry to level 3 triage up to file creation was 24.8 minutes before interventions, and the same was 19.6 minutes for small groups and 17.6 for group training category (p<0.05), pointing to the fact that the group training category showed a significant reduction in average time from patient entry to triage to file creation. Conclusion:The present study found that the training of nurses is practical for the flow times of patients hospitalized in emergency wards.